The Effect Opavrim Injection of Different Dosage to The Ovulation excibility, fertiliti, and the survival of larva ingir-ingir (Mystus nigriceps) - Utami, Risa Tri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted from Mei to Juli 2016 at Fish Breeding and Hatchery Laboratory Fisheris and Marine Science Faculty of Riau University. It was on to know the effect opavrim injection by different doses of the ovulation excitability, fartyliti, and the survival of larva ingir-ingir, as well as knowing which doses of ovaprim are best to produce the ovulation excitability, fertyliti, and the survival of larva ingir-ingir. It the research experiment method was applied with four treatmens and tree replications. The treatment fisiologis solution 0,9 %, Opavrim 0,5 ml/kg. 0,7 ml/kg and 0,9 ml/kg weigh of fish. The result showed that treatment with different dosage of ovaprim provide a significant influence on total of latency time of spawning, eggs ovulation/g weight of fish, eggs diameter, fertilization, egg hatchability and survival rate of larval. The best result was got from 0,7 ml/kg dosage with latency time 6,38 hour, total eggs ovulated 301/g weight of fish, accretion diameter of egg 0,026 mm, egg fertilized 68 %, egg hatchability 55,2 % and survival rate of living larvae was 67,9 %.Water quality during experiment was always in good condition for living.Keyword : Mystus nigriceps, Ovaprim, Fertility, Ovulation, Survival Rate